PERANCANGAN STRATEGI KEBIJAKAN PENGEMBANGAN PELABUHAN TANJUNG PERAK DALAM USAHA MENDUKUNG PERTUMBUHAN PEREKONOMIAN JAWA TIMUR - Kusuma, L. Tri Wijaya Nata; Hamdala, Ihwan (JEMIS (Journal of Engineering & Management in Industrial System), 2014)
Marine port as one important aspect of transportation network set particularly in marine field, should be able to support  transportation  activities or human and good transport from a place (hinterland) to another (foreland). Selection of port that could give best service would be one of important decision issues which would be giving positive impact toward regional economy surrounding the port in particular, and the nation in general. This study has taken object of Tanjung Perak port in Surabaya, particularly in container terminal. Policy development for regional economic growth in surrounding areas of the port was modeled  by using dynamic system approach. Dynamic system approach could solve  complex problems which cannot be solve by mathematical approach. Based on causal loop diagram, it is draw a dynamic system model such as stock and flow diagram to found out impact of changes in each variables affecting the system. Analysis result showed  that economic growth rate in port was affected by several variables, in which port management has the authority to decide policies relevant with those variables. Thus, to increase regional economic growth in port surroundings, appropriate policy scenario to be initiated was to increase pier capacity and by adjusting tariff or retribution.